2022
DOI: 10.3390/healthcare10091596
|View full text |Cite
|
Sign up to set email alerts
|

Food Bolus Properties in Relation to Dentate and Prosthetic Status

Abstract: The objective of this study is to evaluate food bolus properties (mass, moisture content and food comminution) in patients wearing fixed or removable dental prostheses. Methods: A cross-sectional study was conducted on a convenience sample of patients aged at least 55 years old. Patients chewed a 10 g sample of fresh raw carrot until they felt ready to swallow. The mass of the food bolus was determined as collected and after drying. Food comminution was assessed by the multiple sieve method. Results: Patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…MDIs have certain advantages compared to conventional implants: studies have demonstrated the occurrence of lower stresses, the smaller diameter and the resilience offered by the attachment system, which allow the comparison of MDIs behavior to a stress breaker [ 29 ]. Moreover, the presence of conventional implants or MDIs improves the stability of the denture and, implicitly, functional efficiency in the preparation of the food bowl [ 32 ]. The denture design must cover the entire support area of the prosthetic field, and meet all the clinical and technical conditions for the realization of such a prosthodontic restoration; one of the most important parameters to consider is the type of connection with the implant, occlusal scheme and marginal adaptation [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MDIs have certain advantages compared to conventional implants: studies have demonstrated the occurrence of lower stresses, the smaller diameter and the resilience offered by the attachment system, which allow the comparison of MDIs behavior to a stress breaker [ 29 ]. Moreover, the presence of conventional implants or MDIs improves the stability of the denture and, implicitly, functional efficiency in the preparation of the food bowl [ 32 ]. The denture design must cover the entire support area of the prosthetic field, and meet all the clinical and technical conditions for the realization of such a prosthodontic restoration; one of the most important parameters to consider is the type of connection with the implant, occlusal scheme and marginal adaptation [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The finite element partitioning was a compromise between the accuracy of the discretization and the computational possibilities. The loading was the pressure on the surface of these cylinders, so that the total equivalent force was 150 N [ 23 , 27 , 29 ]. To simulate some clinical aspects, the application of pressure was carried out as follows: on the incisal surfaces of the frontal teeth, a clinical situation specific to the action of cutting food; bilaterally, on the occlusal surfaces of the lateral teeth, a situation that corresponded to the maximum intercuspation position and deglutition; unilaterally, on the occlusal surfaces of the lateral teeth, a situation that corresponded to unilateral chewing action.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is suggested that people with a high level of dental anxiety are at risk to become wearers of removable prostheses. This alternative is not always the most indicated when compared with other variants, in regard to several aspects such as oral health-related quality of life or masticatory performance [23][24][25]. In this study, participants who had removable denture treatment had a higher chance of responding affirmatively to "fear of going to the dentist significantly affects my life in some way (dental pain, avoiding eating some foods, embarrassed or self-conscious about appearance of teeth or mouth, etc.)".…”
Section: Discussionmentioning
confidence: 99%